2017
DOI: 10.2174/1874613601711010052
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease and Cardiovascular Disease Risk in HIV-Positive Populations in the Asian Region

Abstract: Introduction:Cardiovascular diseases (CVD) are becoming more prevalent in HIV-infected populations as they age largely due to improved treatment outcomes. Assessment of CVD risk and CVD risk factors in HIV-positive populations has focused on high income settings, while there are limited studies evaluating CVD in HIV-positive populations in the Asian region.Materials and Methods:We provided an overview of the prevalence and incidence of CVD and its risk factors in adult HIV-positive populations, and of the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(85 reference statements)
0
8
0
1
Order By: Relevance
“…However, most of these studies have been confined to Western populations [1, 512, 1517]. Little is known regarding the association between HIV infection and the risk of stroke in Asian people [6, 13, 14]. Multiple factors, including age, sex, family history, the effect of HIV itself, the effect of antiretroviral therapy, traditional cardiovascular risk factors etc., influence the risk of stroke in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies have been confined to Western populations [1, 512, 1517]. Little is known regarding the association between HIV infection and the risk of stroke in Asian people [6, 13, 14]. Multiple factors, including age, sex, family history, the effect of HIV itself, the effect of antiretroviral therapy, traditional cardiovascular risk factors etc., influence the risk of stroke in HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of lipid levels as a risk factor for CVDs in PLWH in Asian regions (including Korea) reported that dyslipidemia was less prevalent in patients who first presented with HIV compared with in HIV-negative controls. In addition, total cholesterol levels were on average lower in HIV-positive patients, whereas findings were inconsistent regarding triglyceride levels [ 26 ]. This review also showed that ART had an unfavorable effect on blood lipid levels in Asian PLWH [ 26 ].…”
Section: Dyslipidemia and Artmentioning
confidence: 99%
“…There is some guidance for CVD risk prevention and management in PLWH in Asia provided through national HIV treatment guidelines; however, these are limited in number and scope [13]. The recommendations below are based on existing data from research on CVD in PLWH, particularly those from Asia where available.…”
Section: Management Of Cvd Riskmentioning
confidence: 99%
“…Regardless of HIV status, about 50% of CVD deaths worldwide occur in Asia [10]. Asian PLWH have a high prevalence of conventional risk factors for CVD, such as smoking, dyslipidaemia, hypertension and insulin resistance or diabetes mellitus [11][12][13]. Currently, there is limited but growing interest in the research on CVD in Asian PLWH.…”
Section: Introductionmentioning
confidence: 99%